NEW TECHNOLOGIES AND THE CHALLENGE FOR EDUCATIONAL LEADERSHIP - Balalle, Himendra; Weerasinghe, Tudor (International Journal of Academic Research and Reflection, 2021)
The position of education technology today, above all, is of great importance. Whether colleges or universities, teachers are not qualified to use the equipment themselves Whether they realise its advantages of Education? Education technology is a systematic, organised solution to digital technology to increase education efficiency. It is a systematic tool for planning and reviewing educational practices, reading and coaching, and introducing modern teaching methods. It needs teaching materials, methods and coordination of operation, and all participants' activities in the education process. This research centred on how technology inclusion emerges in Education and how education practitioners address such a transition phase's complexities and resolve them. Study results would be beneficial for all educational organisations when the education sector experiences a significant technical change.
Keywords: Education Technology; Technology and Learning; Educational Leadership; Online Learning